THE The Relationship Between Knowledge and Attitude on Hba1c Levels in Type 2 Diabetes Mellitus Patients in The Working Area of Made Health Center Surabaya - Mohamad, Fawaid; Imam Santosa, Rahajoe; Pribadi, Florence (Bahasa Indonesia, 2025)
Non-communicable diseases (NCDs) have become the focus of world leaders, especially diabetes mellitus. (DM). Through inflammatory processes such as the formation of free fatty acids and adipokine imbalance, adipose tissue contributes to increased insulin resistance. The city of Surabaya has the highest number of DM patients in East Java, with 102,599 DM patients in 2017 and 115,460 DM patients in 2018. The objective of this study is to determine the relationship between knowledge and attitudes towards the prevention of the progression of type 2 diabetes mellitus in the working area of the Made Health Center in Surabaya. This research uses a cross-sectional approach with the chi-square statistical test method. The results of this study indicate that there is a relationship between knowledge and HbA1c levels (p = 0.035) and for the relationship between attitude and HbA1c levels (p = 0.888). This study can be concluded that there is a relationship between knowledge and HbA1c levels and there is no relationship between attitude and HbA1c levels.